Controversia en torno a la figura de Kate en "The Taming of the Shrew" de William Shakespeare - Romero López, Alicia (Tropelías: Review of Literary Theory and Comparative Literature, 2015)
Este artículo pretende aportar una nueva mirada sobre el personaje de Katherina en la obra The Taming of the Shrew de William Shakespeare. Este personaje femenino es en gran manera controvertido por la violencia y la sumisión a la que se ve sometido. En este trabajo se analizará si realmente estamos ante una mujer sometida o si, más bien, el texto nos presenta a una mujer que se escapa a las constricciones sociales de la época. Para ello tendremos en cuenta no solo el contexto histórico en el que se enmarca la obra, si no que se hará una breve revisión de las representaciones más importantes de esta obra en España (1947-2008), para señalar cómo el personaje de Katherina, y lo que este representa, varía en función de la época y la representación. This article offers a new perspective on the William Shakespeare’s Kate in the The Taming of the Shrew. This female figure has been the subject of much controversy because of the violence and degradation to which she is subjected. This article questions whether we are presented with an oppressed woman, or whether in fact the text shows a woman who escapes the social constraints of the period. As part of this discussion the article not only discusses the historical period in which the play takes place, but also makes a brief summary of the most important Spanish productions of this play during the period (1947-2008), in order to show that Kate’s character and what she represents differs according to each production and its social context.